Availability and affordability of priority life-saving medicines for under-five children in health facilities of Tigray region, northern Ethiopia - Solomon Abrha; Ebisa Tadesse; Tesfay Mehari Atey; Fantahun Molla; Wondim Melkam; Birhanetensay Masresha; Solomon Gashaw; Abrham Wondimu (BMC, 2018)
Abstract Background In developing countries, child health outcomes are influenced by the non-availability of priority life-saving medicines at public sector health facilities and non-affordability of medicines at private medicine outlets. This study aimed to assess availability, price components and affordability of priority life-saving medicines for under-five children in Tigray region, Northern Ethiopia. Methods A cross-sectional study was conducted in Tigray region from December 2015 to July 2016 using a standard method developed by the World Health Organization and Health Action International (WHO/HAI). Data on the availability and price of 27 priority life-saving medicines were collected from 31 public and 10 private sectors. Availability and prices were expressed in percent and median price ratios (MPRs), respectively. Affordability was reported in terms of the daily wage of the lowest-paid unskilled government worker. Results The overall availability of priority life-saving drugs in this study was low (34.1%). The average availabilities of all surveyed medicines in public and private sectors were 41.9 and 31.5%, respectively. The overall availability of medicines for malaria was found to be poor with average values of 29.3% for artemisinin combination therapy tablet, 19.5% for artesunate injection and 0% for rectal artesunate. Whereas, the availability of oral rehydration salt (ORS) and zinc sulphate dispersible tablets for the treatment of diarrhea was moderately high (90% for ORS and 82% for zinc sulphate). Medicines for pneumonia showed an overall percent availability in the range of 0% (ampicillin 250 mg and 1 g powder for injection and oxygen medicinal gas) to 100% (amoxicillin 500 mg capsule). The MPRs of 12 lowest price generic medicines were 1.5 and 2.7 times higher than the international reference prices (IRPs) for the private and public sectors, respectively. About 30% of priority life-saving medicines in the public sector and 50% of them in the private sector demanded above a single daily wages to purchase the standard treatment of the prevalent diseases of children. Conclusions The lower availability, high price and low affordability of lowest price generic priority life-saving medicines in public and private sectors reflect a failure to implement the health policy on priority life-saving medicines in the region.